Impact of hemophilia B on quality of life in affected men, women, and caregivers—Assessment of patient‐reported outcomes in the B‐HERO‐S study. (11th April 2018) - Buckner, Tyler W.; Witkop, Michelle; Guelcher, Christine; Sidonio, Robert; Kessler, Craig M.; Clark, David B.; Owens, Wendy; Frick, Neil; Iyer, Neeraj N.; Cooper, David L.
Abstract: Introduction: Health‐related quality of life (HRQoL) is impaired in patients with hemophilia; however, the impact in mild/moderate hemophilia B and affected women is not well characterized. Objective: To evaluate factors that affect HRQoL in adults with hemophilia B and caregivers of affected children. Methods: US adult patients and caregivers of affected children completed distinct 1‐hour online surveys including patient‐reported outcome instruments. Results: In total, 299 adult patients and 150 caregivers participated. Adults with moderate hemophilia reported poorer health status (median EQ‐5D‐5L index score, 0.63) than those with mild (0.73) or severe (0.74) hemophilia. Women reported greater pain severity than men on the Brief Pain Inventory v2 Short Form (median, 7.00 vs 5.00). Based on the Patient Health Questionnaire, mild or worse depression was observed in >50% of adult respondents, and depression was reported more often in those with moderate and severe hemophilia vs those with mild hemophilia. Most caregivers reported at least mild depression. Conclusion: Pain, functional impairment, and depression/anxiety are present at higher‐than‐expected levels in individuals with hemophilia B. The large proportion of individuals with mild/moderate hemophilia and women with reduced health status suggests significant unmet needs in this population.